Crosslinked polyethylene insulating material with intrinsic self-repairing and recoverable characteristics as well as preparation method and application of crosslinked polyethylene insulating material

Through catalytic amination reaction and post-absorption treatment, the crosslinked polyethylene insulating material is functionally modified to form a material with self-healing and recyclable characteristics, solving the problem of difficult materials self-healing and recycling in the prior art, and achieving long-term reliable operation of materials and efficient recycling of resources.

CN119798727AActive Publication Date: 2025-04-11UNIV OF SCI & TECH BEIJING

Patent Information

Application Number
CN202411811574.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-11
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

Crosslinked polyethylene insulating materials are difficult to self-repair after damage, and chemical crosslinking networks make it impossible to recycle and process them through simple thermoplastic processing, resulting in waste of resources and environmental pollution.

Method used

The low-density polyethylene is functionally modified by catalytic amination reaction, and small furyl molecules and peroxides are introduced, and post-absorption treatment and hot pressing treatment are carried out to form a crosslinked polyethylene insulating material with dynamic reversible properties.

Benefits of technology

It realizes self-repairing ability after electrical and mechanical damage, as well as recyclable and reuse characteristics after retirement, and improves the comprehensive performance and environmental friendliness of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798727A_ABST
    Figure CN119798727A_ABST
Patent Text Reader

Abstract

The invention provides a crosslinked polyethylene insulating material with intrinsic self-repairing and recoverable characteristics as well as a preparation method and application thereof, and relates to the technical field of cable materials. The crosslinked polyethylene insulating material with intrinsic self-repairing and recoverable characteristics is prepared from the following components in parts by weight: 99.7 parts by weight of low-density polyethylene, 1.0 to 2.6 parts by weight of peroxide, 0.1 to 0.5 part by weight of an antioxidant, 5 to 20 parts by weight of a maleimide monomer, 0.35 to 0.7 part by weight of a catalyst, 0.5 to 3.0 parts by weight of a ligand and 0.5 to 3.0 parts by weight of furyl micromolecules. The low-density polyethylene is subjected to functional modification through catalytic amination reaction, chain interruption and crosslinking in the modification process are avoided, and the mechanical property, the insulating property and the dielectric property of the crosslinked polyethylene are enhanced through peroxide introduced through post-absorption. Meanwhile, the dynamic reversible Diels-Alder reaction introduced by the furyl small molecules is absorbed, so that the polyethylene insulating material has a good intrinsic self-repairing effect on mechanical damage and electric damage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cable materials, and in particular to a cross-linked polyethylene insulating material with intrinsic self-repairing and recyclable properties, and a preparation method and application thereof. Background Art

[0002] Cross-linked polyethylene (XLPE) is an insulating material widely used in the modern cable industry. Due to its excellent electrical properties, heat resistance and mechanical strength, it has become the first choice for high-voltage and ultra-high-voltage cables. However, the cross-linked structure of XLPE material is irreversible and difficult to repair and recycle, which brings many problems in actual use and waste disposal.

[0003] During the service of XLPE cables, microcracks or local damage may occur in the XLPE insulation layer due to mechanical stress, electrical tree effect or thermal aging. These defects may further develop into breakdown paths, significantly shortening the life of the cable. Existing XLPE materials generally rely on irreversible chemical cross-linking and lack self-repairing ability. Insulation performance can only be restored through complex repair processes (such as replacing damaged parts or re-injecting external repair agents or microcapsules, such as the invention patent with publication number CN106750829A, which achieves self-repair of electrical tree defects by introducing microcapsules inside cross-linked polyethylene) to increase maintenance difficulty and cost. In addition, the chemical cross-linking network of XLPE makes it impossible to recycle it through simple thermoplastic processing, which not only causes a large amount of waste of resources of discarded cables, but also brings serious environmental pollution problems. At present, the recycling of XLPE materials is mainly decomposed into small molecular compounds through high-energy consumption cracking methods, with low recycling efficiency and easy to produce secondary pollution.

[0004] Therefore, how to achieve the intrinsic self-repair of cross-linked polyethylene insulation materials after damage and their recycling and reuse after retirement has become a major problem in the existing technology. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention aims to provide a cross-linked polyethylene insulation material and a preparation method and application thereof. The cross-linked polyethylene cable insulation material has the characteristics of self-repair after electrical and mechanical damage and can be recycled after retirement.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] A cross-linked polyethylene insulation material with intrinsic self-repairing and recyclable properties is prepared from the following components in parts by weight:

[0008] 99.7 parts by weight of low-density polyethylene, 1.0-2.6 parts by weight of peroxide, 0.1-0.5 parts by weight of antioxidant, 5-20 parts by weight of maleimide monomer, 0.35-0.7 parts by weight of catalyst, 0.5-3.0 parts by weight of ligand, and 0.5-3.0 parts by weight of furan-based small molecule.

[0009] Preferably, the catalyst is one of copper chloride and copper iodide; the ligand is 1,10-phenanthroline; the furanyl small molecule is one of 2,2-di(2-tetrahydrofuranyl)propane, bis(2-methyl-3-furanyl)disulfide, di(2-furanyl)chlorophosphine and tri(2-furanyl)phosphine; the peroxide is one of diisopropylbenzene peroxide, di(hexadecyl)dicarbonate and di-tert-butyl peroxide.

[0010] Preferably, the number average molecular weight of the low-density polyethylene is 10,000-100,000 g / mol, and it has excellent flexibility and processability.

[0011] The present invention also provides a method for preparing a cross-linked polyethylene insulating material having intrinsic self-repairing and recyclable properties, comprising the following steps:

[0012] (1) low-density polyethylene, peroxide, antioxidant, maleimide monomer, catalyst, ligand and solvent are mixed to carry out catalytic amination reaction, and after the reaction, the mixed solution is poured into a methanol solution for cooling and reduction elimination, and then dried to obtain a functionalized polyethylene material;

[0013] (2) The functionalized polyethylene obtained in step (1) is mixed with furan-based small molecules and peroxide, and then subjected to post-absorption treatment and hot pressing treatment in sequence to obtain a cross-linked polyethylene insulation material.

[0014] Preferably, in step (1), the ratio of the mass of maleimide monomer to the total mass of low-density polyethylene and antioxidant is (5-20):100; the ratio of the mass of peroxide to the total mass of low-density polyethylene and antioxidant is (1.0-2.6):100; the ratio of the mass of the catalyst to the total mass of low-density polyethylene and antioxidant is preferably (0.35-0.7):100; the ratio of the amount of substance of the ligand to the amount of substance of the catalyst is 1:1; the ratio of the mass of the antioxidant to the total mass of low-density polyethylene and antioxidant is (0.1-0.5):100.

[0015] Preferably, in step (1), the catalyst is one of copper chloride and copper iodide.

[0016] Preferably, in step (1), the solvent is one of toluene, o-dichlorobenzene and p-xylene.

[0017] Preferably, in step (1), the ligand is 1,10-phenanthroline.

[0018] Preferably, in step (1), the peroxide is one of dicumyl peroxide, di(hexadecyl) dicarbonate peroxide and di-tert-butyl peroxide.

[0019] Preferably, in step (1), the temperature of the catalytic amination reaction is 115-125° C., and the time of the catalytic amination reaction is 80-120 min.

[0020] Preferably, in step (1), the drying temperature is 60-80° C. and the drying time is 12-24 hours.

[0021] Preferably, in step (2), the furanyl small molecule is one of 2,2-di(2-tetrahydrofuranyl)propane, bis(2-methyl-3-furanyl)disulfide, di(2-furanyl)phosphine chloride and tri(2-furanyl)phosphine.

[0022] Preferably, in step (2), the ratio of the mass of the furan-based small molecule to the total mass of the low-density polyethylene and the antioxidant is (0.5-3.0):100.

[0023] Preferably, in step (2), the ratio of the mass of peroxide to the total mass of low-density polyethylene and antioxidant is (1.0-2.6):100.

[0024] Preferably, in step (2), the order of post-absorption is furanyl small molecules and peroxide, the temperature of post-absorption treatment is 60-80° C., and the time of post-absorption treatment is 12-28 hours.

[0025] Preferably, in step (2), the temperature of the hot pressing treatment is 120-180° C., and the hot pressing time is 6-120 min.

[0026] The present invention also provides application of the cross-linked polyethylene insulation material with intrinsic self-repairing and recyclable functions in the field of cable insulation materials.

[0027] The technical solution of the present invention has the following beneficial effects:

[0028] The present invention provides a cross-linked polyethylene insulating material with intrinsic self-repairing and recyclable properties. Functional modification of low-density polyethylene is performed by catalytic amination reaction, thereby avoiding chain breakage and cross-linking during the modification process, and the mechanical properties, insulation properties and dielectric properties of the cross-linked polyethylene are enhanced by the peroxide introduced by post-absorption. At the same time, the dynamic reversible Diels-Alder reaction introduced by the post-absorption furanyl small molecules enables the polyethylene insulating material of the present invention to have a good intrinsic self-repairing effect on mechanical damage and electrical damage, and can also be recycled and reused after retirement, which is of great significance for the long-term reliable operation of cables and resource recycling. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0030] Figure 1 The Fourier transform infrared spectra of the cross-linked polyethylene prepared in Examples 1 to 3 of the present invention and Comparative Example 1;

[0031] Figure 2 The SEM images of the cross-linked polyethylene prepared in Example 1 of the present invention after mechanical and corona damage and self-repair, wherein (a) is a SEM image after mechanical damage, (b) is a SEM image of repair after mechanical damage, (c) is a SEM image of corona damage, and (d) is a SEM image of repair after corona damage;

[0032] Figure 3 The stress-strain curve of the cross-linked polyethylene prepared in Example 1 of the present invention before and after mechanical damage repair;

[0033] Figure 4 The stress-strain curves of the cross-linked polyethylene prepared in Example 1 of the present invention after different mechanical and solution recycling times. DETAILED DESCRIPTION

[0034] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0035] The present invention provides a method for preparing a cross-linked polyethylene insulating material having intrinsic self-repairing and recyclable properties, comprising the following steps:

[0036] (1) low-density polyethylene, peroxide, antioxidant, maleimide monomer, catalyst, ligand and solvent are mixed to carry out catalytic amination reaction, and after the reaction, the mixed solution is poured into a methanol solution for cooling and reduction elimination, and then dried to obtain a functionalized polyethylene material;

[0037] (2) The functionalized polyethylene obtained in step (1) is mixed with furan-based small molecules and peroxide, and then subjected to post-absorption treatment and hot pressing treatment in sequence to obtain a cross-linked polyethylene insulation material.

[0038] Unless otherwise specified, the present invention has no particular limitation on the sources of the components, and commercially available products known to those skilled in the art may be used.

[0039] The invention mixes low-density polyethylene, peroxide, antioxidant, maleimide monomer, catalyst, ligand and solvent to carry out catalytic amination reaction.

[0040] In the present invention, the ratio of the mass of the maleimide monomer to the total mass of the low-density polyethylene and the antioxidant is preferably (5-20):100, that is, the mass of the maleimide monomer: the mass of (low-density polyethylene + antioxidant) is (5-20):100, more preferably (10-15):100. The present invention limits the mass of the maleimide monomer to the above range, which can adjust the structure of polyethylene and enhance the mechanical properties and insulation properties of the functionalized polyethylene.

[0041] In the present invention, the catalyst is preferably copper chloride and copper iodide, more preferably copper iodide. By combining with the ligand, the chain breaking and crosslinking of low-density polyethylene during the catalytic amination process can be inhibited to ensure that the molecular weight of the functionalized polyethylene does not change significantly.

[0042] In the present invention, the ratio of the mass of the catalyst to the total mass of the low-density polyethylene and the antioxidant is preferably (0.35-0.7):100, that is, the mass of the catalyst: the mass of (low-density polyethylene + antioxidant) is (0.35-0.7):100, more preferably 0.35:100. The present invention limits the ratio of the mass of the catalyst to the total mass of the low-density polyethylene and the antioxidant to the above range, which can ensure the smooth progress of the catalytic amination reaction to achieve the functionalization of the material, while making the insulating material have higher insulation performance.

[0043] In the present invention, the ratio of the amount of the ligand to the amount of the catalyst is preferably 1: 1. The present invention limits the amount of the ligand to the catalyst within the above range, which can inhibit chain breaking and crosslinking of low-density polyethylene during catalytic amination and ensure that the molecular weight of the functionalized polyethylene does not change significantly.

[0044] In the present invention, the ratio of the mass of the antioxidant to the mass of the low-density polyethylene and the antioxidant is (0.1-0.5):100, that is, the mass of the antioxidant: the mass of (low-density polyethylene+antioxidant) is (0.1-0.5):100.

[0045] In the present invention, the solvent is preferably toluene, o-dichlorobenzene and p-xylene, and more preferably o-dichlorobenzene. The high boiling point of o-dichlorobenzene solvent is used to promote the full dissolution of low-density polyethylene, so that the catalytic amination reaction can be carried out more fully.

[0046] In the present invention, the temperature of the catalytic amination reaction is preferably 115°C to 125°C, more preferably 120°C; the reaction time of the catalytic amination is preferably 80min to 120min, more preferably 90min. The present invention limits the catalytic amination temperature and time within the above ranges, which can make the amination process more fully carried out.

[0047] In the present invention, the catalytic amination reaction is preferably carried out in an air atmosphere.

[0048] In the present invention, after the catalytic amination reaction, the mixed solution is poured into a methanol solution to be cooled, and a reduction elimination operation is performed to obtain a functionalized polyethylene material.

[0049] In the present invention, the reduction elimination time is preferably 60 min to 180 min, more preferably 120 min.

[0050] In the present invention, the cooling and reduction elimination are preferably natural cooling, and the end point of the cooling is preferably room temperature.

[0051] In the present invention, the drying is preferably vacuum drying, the drying temperature is preferably 70° C., and the drying time is preferably 12 h.

[0052] After obtaining the functionalized polyethylene material, the present invention performs a post-absorption treatment of furanyl small molecules and peroxide on the functionalized polyethylene material, and then performs a hot pressing treatment to obtain a dynamically cross-linked polyethylene insulation material.

[0053] In the present invention, the furanyl small molecule is preferably 2,2-bis(2-tetrahydrofuranyl)propane, bis(2-methyl-3-furanyl)disulfide, di(2-furanyl)phosphine chloride and tri(2-furanyl)phosphine, more preferably bis(2-methyl-3-furanyl)disulfide and tri(2-furanyl)phosphine, and most preferably bis(2-methyl-3-furanyl)disulfide. In the present invention, bis(2-methyl-3-furanyl)disulfide not only has the furanyl group capable of undergoing Diels-Alder reaction with maleimide, but also contains a dynamic disulfide bond, which can further improve the dynamic reversibility of the cross-linked polyethylene material and enhance the self-repair and recycling properties of the cross-linked polyethylene material.

[0054] In the present invention, the peroxide is preferably dicumyl peroxide, di(hexadecyl) dicarbonate and di-tert-butyl peroxide, more preferably dicumyl peroxide and di-tert-butyl peroxide, and most preferably dicumyl peroxide.

[0055] In the present invention, the order of the post-absorption treatment is bis(2-methyl-3-furyl) disulfide and diisopropylbenzene peroxide.

[0056] In the present invention, the ratio of the mass of the furan-based small molecule to the total mass of the low-density polyethylene and the antioxidant is preferably (0.5-3.0): 100, that is, the mass of the furan-based small molecule: the mass of (low-density polyethylene + antioxidant) is (0.5-3.0): 100, more preferably (1.0-2.0): 100, and most preferably 1.5: 100. The present invention limits the mass ratio of the furan-based small molecule to the total mass of the low-density polyethylene and the antioxidant within the above range, which can effectively retain the mechanical properties and insulation properties of the cross-linked polyethylene, while giving the cross-linked polyethylene self-repairing and recycling properties.

[0057] In the present invention, the ratio of the mass of the peroxide to the total mass of the low-density polyethylene and the antioxidant is preferably (1.0-2.6):100, that is, the mass of the peroxide: the mass of (low-density polyethylene + antioxidant) is (0.5-3.0):100, more preferably (1.2-2.2):100, and most preferably 1.8:100. The present invention limits the mass ratio of the peroxide to the total mass of the low-density polyethylene and the antioxidant to the above range, and by changing the mass of the peroxide and adjusting the ratio of covalent crosslinking and dynamic crosslinking, the comprehensive performance of the crosslinked polyethylene can be improved.

[0058] In the present invention, the temperature of the post-absorption treatment is preferably 60°C to 80°C, more preferably 70°C; the time of the post-absorption treatment is preferably 12h to 28h, more preferably 24h. The present invention limits the temperature and time of the post-absorption treatment to the above range, which can promote the functionalized polyethylene material to more fully absorb furanyl small molecules and peroxides.

[0059] In the present invention, the temperature of the hot pressing treatment is preferably 120°C to 180°C, and the hot pressing time is preferably 6 to 120 minutes; more preferably, hot pressing at 120°C for 6 minutes and hot pressing at 140°C for 120 minutes. The present invention limits the temperature and time of the hot pressing treatment to the above ranges, so that the Diels-Alder reaction and the covalent cross-linking reaction can be fully carried out to obtain a cross-linked polyethylene insulating material.

[0060] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0061] Example 1

[0062] 99.7 parts by weight of low-density polyethylene (whose number average molecular weight is 17371 g / mol) and 0.2 parts by weight of antioxidant 300 are added to o-dichlorobenzene solvent at 30°C, then heated to 120°C and mechanically stirred until completely dissolved; then 1.8 parts by weight of diisopropylbenzene peroxide, 15 parts by weight of maleimide monomer, 0.35 parts by weight of copper iodide catalyst, and 1.46 parts by weight of 1,10-phenanthroline ligand are added to the mixed solution in sequence (the mass of maleimide monomer is 1 / 2 of the total mass of low-density polyethylene plus antioxidant). The ratio is 15:100, the mass ratio of copper iodide to the total mass of low-density polyethylene plus antioxidant is 0.35:100, and the molar ratio of copper iodide to 1,10-phenanthroline is 1:1), and mechanically stirred at 120°C in an air atmosphere for 90 minutes to obtain a homogeneous viscous functionalized polyethylene solution, and then the above solution is poured into 30 mL of methanol solution, stirred for 120 minutes, allowed to cool naturally, filtered and then vacuum dried, placed in a vacuum drying oven at 70°C for 12 hours, and naturally cooled to obtain a functionalized polyethylene material. Subsequently, 1.5 parts by weight of bis(2-methyl-3-furanyl) disulfide and 1.8 parts by weight of diisopropylbenzene peroxide were added to the functionalized polyethylene material for post-absorption treatment (the total mass ratio of bis(2-methyl-3-furanyl) disulfide to low-density polyethylene plus antioxidant was 1.5:100, and the total mass ratio of diisopropylbenzene peroxide to low-density polyethylene plus antioxidant was 1.8:100), first stirred at 30°C for 30 minutes, then placed in a 70°C forced drying oven for 30 minutes, and the above operation was repeated 4 times and then placed in a 70°C forced drying oven for 20 hours. Finally, the material after post-absorption treatment was subjected to hot pressing pretreatment at 120°C for 6 minutes and hot pressing treatment at 140°C for 120 minutes to obtain a cross-linked polyethylene insulation material, which was recorded as DPPE1.

[0063] Example 2

[0064] The mass of bis(2-methyl-3-furyl) disulfide in Example 1 was replaced with 2.0 parts by weight. At this time, the total mass ratio of bis(2-methyl-3-furyl) disulfide to low-density polyethylene plus antioxidant was 2.0:100. Other parameters were the same as those in Example 1, and a cross-linked polyethylene insulation material was obtained, which was recorded as DPPE2.

[0065] Example 3

[0066] The mass of bis(2-methyl-3-furyl) disulfide in Example 1 was replaced with 2.5 parts by weight. At this time, the total mass ratio of bis(2-methyl-3-furyl) disulfide to low-density polyethylene plus antioxidant was 2.5:100. Other parameters were the same as in Example 1, and a cross-linked polyethylene insulation material was obtained, which was recorded as DPPE3.

[0067] Comparative Example 1

[0068] A cross-linked polyethylene insulated cable, which is different from Example 1 in that the polyethylene is not subjected to functional modification and post-absorption of furanyl small molecules according to the modification method described in Example 1. The specific method is: 99.7 parts by weight of low-density polyethylene and 0.2 parts by weight of antioxidant are mixed, and then 1.8 parts by weight of diisopropylbenzene peroxide are added for post-absorption treatment (the ratio of diisopropylbenzene peroxide to the total mass of low-density polyethylene plus antioxidant is 1.8:100). Finally, the material after post-absorption treatment is subjected to hot pressing pretreatment at 120°C for 6 minutes and hot pressing treatment at 140°C for 120 minutes in sequence to obtain a cross-linked polyethylene insulation material, which is recorded as XLPE.

[0069] Comparative Example 2

[0070] 99.7 parts by weight of low-density polyethylene and 0.2 parts by weight of an antioxidant were uniformly mixed, and then subjected to a hot pressing pretreatment at 120° C. for 6 min and a hot pressing treatment at 140° C. for 120 min in sequence to obtain a low-density polyethylene material, which was recorded as LDPE.

[0071] Comparative Example 3

[0072] 99.7 parts by weight of low-density polyethylene and 0.2 parts by weight of antioxidant are added to o-dichlorobenzene solvent at 30°C, then heated to 120°C and mechanically stirred until completely dissolved; then 1.8 parts by weight of peroxide, 15 parts by weight of maleimide monomer, 0.35 parts by weight of catalyst and 1.46 parts by weight of ligand are added to the mixed solution in sequence (the ratio of the mass of maleimide monomer to the total mass of low-density polyethylene plus antioxidant is 15:100, the ratio of the mass of catalyst to the total mass of low-density polyethylene plus antioxidant is 0.35:100, and the molar ratio of catalyst to ligand is 1:1), and mechanically stirred at 120°C in an air atmosphere for 90 minutes to obtain a homogeneous viscous functionalized polyethylene solution, and then the solution is poured into a methanol solution, stirred for 120 minutes to allow it to cool naturally, filtered and vacuum dried, placed in a vacuum drying oven at 70°C for 12 hours, and naturally cooled to obtain a functionalized polyethylene material. Subsequently, the functionalized polyethylene material was subjected to a hot pressing pretreatment at 120°C for 6 min and a hot pressing treatment at 140°C for 120 min in sequence to obtain a functionalized low-density polyethylene material, which was denoted as CAPE.

[0073] Compared with Example 1, Comparative Example 2 is a low-density polyethylene that has not been modified by catalytic amination reaction and post-absorption treatment, and is only a low-density polyethylene insulating material; compared with Example 1, Comparative Example 3 is a functionalized polyethylene material modified by catalytic amination, without post-absorption and hot-pressing cross-linking.

[0074] Table 1 Material properties of Example 1, Comparative Example 2 and Comparative Example 3

[0075]

[0076] Table 1 records the material properties of Example 1, Comparative Example 2 and Comparative Example 3. It can be seen from Table 1 that the mechanical properties and breakdown strength of the cross-linked polyethylene insulation material prepared in Example 1 are significantly improved compared with the non-cross-linked Comparative Example 2 and Comparative Example 3, and Example 1 also has good self-repair and recyclability. It can be seen from the comparison of the mechanical properties of Comparative Example 2 and Comparative Example 3 that the tensile strength and elongation at break of the sample are basically unchanged before and after catalytic amination, which confirms that the polyethylene does not undergo chain scission and cross-linking during the catalytic amination reaction.

[0077] The Fourier transform infrared spectra of the cross-linked polyethylene prepared in Examples 1 to 3 and the comparative example were tested. The cross-linked polyethylene prepared was cut into small pieces of 30 mm × 30 mm and tested using a Fourier transform infrared spectrometer with a scanning range of 4000 to 500 cm -1 , the results are as follows Figure 1 By comparing the 1720cm in Examples 1 to 3 and Comparative Example 1 -1 and 810cm -1 The changes in the characteristic absorption peaks at respectively confirmed the grafting of maleimide and the introduction of furanyl small molecules in the catalytic amination reaction.

[0078] The SEM images of the cross-linked polyethylene prepared in Test Example 1 before and after the repair of corona damage were taken. The cross-linked polyethylene prepared was cut into a shape of 70 mm × 70 mm. The surface SEM image of the sample after corona damage was taken after 4 hours of corona at 2.2 kV using a corona resistance test system with a pin plate electrode. The sample after corona damage was then placed in a blast drying oven at 120°C for 12 hours of repair and the surface SEM image of the repaired sample was taken. The results are as follows: Figure 2 (a) and Figure 2 (b). Figure 2 (a) It can be seen that after 4 hours of corona treatment, obvious halo marks appeared on the surface of cross-linked polyethylene, which disappeared after thermal stimulation. Figure 2 (b) shows that it has good self-repair performance after electrical damage.

[0079] The SEM images of the cross-linked polyethylene prepared in Test Example 1 before and after mechanical damage repair were taken. The prepared cross-linked polyethylene was cut into a shape of 10 mm × 50 mm × 10 mm, and a cutter was used to scratch the surface of the sample to a depth of about 7 mm. The surface SEM of the scratched sample was taken, and then the mechanically damaged sample was placed in a 120°C blast drying oven for repair for 12 hours, and the surface SEM image of the repaired sample was taken. The results are as follows: Figure 2 (c) and Figure 2 (d). Figure 2 (c) It can be seen that after cross-linked polyethylene receives severe mechanical damage, it can be effectively repaired by applying thermal stimulation to it, such as Figure 2 As shown in (d), it has good self-repair ability.

[0080] The mechanical properties of the cross-linked polyethylene prepared in Example 1 before and after self-repair were tested. The prepared cross-linked polyethylene was cut into dumbbell-shaped specimens using a mold, and then mechanically damaged (scratched to two-thirds of its thickness). After damage, it was placed in a 120°C blast drying oven for repair for 12 hours, and then the mechanical properties of the specimens before and after mechanical damage were tested using a MARK-10 tester. The speed of the tensile test was 50 mm / min. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the tensile strength of the cross-linked polyethylene prepared in Example 1 recovered to more than 93% of the initial value after self-repair, and the elongation at break recovered to more than 63% of the initial value after self-repair, and the cross-linked polyethylene prepared in Example 1 has good self-repair performance.

[0081] The mechanical properties of the cross-linked polyethylene prepared in Example 1 before and after two mechanical recovery and two solution recovery were tested. The prepared cross-linked polyethylene was cut into dumbbell-shaped specimens using a mold, and the mechanical properties of the specimens before and after two mechanical recovery and solution recovery were tested using a MARK-10 tester. The speed of the tensile test was 50 mm / min. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that the cross-linked polyethylene prepared in Example 1 has a tensile strength of approximately 100% of the initial state after two mechanical recovery, and an elongation at break of approximately 90% of the initial state. After two solution recovery, the tensile strength is approximately 98% of the initial state, and the elongation at break is approximately 80% of the initial state, and has excellent recyclability.

[0082] In summary, the cross-linked polyethylene prepared by the present invention has excellent self-repairing ability after mechanical damage and electrical damage and multiple recyclability.

[0083] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A cross-linked polyethylene insulation material with intrinsic self-repairing and recyclable properties, characterized in that: Prepared from the following components by weight: 99.7 parts by weight of low-density polyethylene, 1.0-2.6 parts by weight of peroxide, 0.1-0.5 parts by weight of antioxidant, 5-20 parts by weight of maleimide monomer, 0.35-0.7 parts by weight of catalyst, 0.5-3.0 parts by weight of ligand, and 0.5-3.0 parts by weight of furan-based small molecule.

2. The cross-linked polyethylene insulation material with intrinsic self-healing and recyclable properties according to claim 1, characterized in that: The catalyst is one of copper chloride and copper iodide; the ligand is 1,10-phenanthroline; the furanyl small molecule is one of 2,2-di(2-tetrahydrofuranyl)propane, bis(2-methyl-3-furanyl)disulfide, di(2-furanyl)chlorophosphine and tri(2-furanyl)phosphine; and the peroxide is one of diisopropylbenzene peroxide, di(hexadecyl)dicarbonate and di-tert-butyl peroxide.

3. A method for preparing a cross-linked polyethylene insulation material having intrinsic self-repairing and recyclable properties, characterized in that: The steps include: (1) low-density polyethylene, peroxide, antioxidant, maleimide monomer, catalyst, ligand and solvent are mixed to carry out catalytic amination reaction, and after the reaction, the mixed solution is poured into a methanol solution for cooling and reduction elimination, and then dried to obtain a functionalized polyethylene material; (2) The functionalized polyethylene obtained in step (1) is mixed with furan-based small molecules and peroxide, and then subjected to post-absorption treatment and hot pressing treatment in sequence to obtain a cross-linked polyethylene insulation material.

4. The method for preparing the cross-linked polyethylene insulation material with intrinsic self-repairing and recyclable properties according to claim 3, characterized in that: In the step (1), the ratio of the mass of the maleimide monomer to the total mass of the low-density polyethylene and the antioxidant is (5-20):100; the ratio of the mass of the peroxide to the total mass of the low-density polyethylene and the antioxidant is (1.0-2.6):100; the ratio of the mass of the catalyst to the total mass of the low-density polyethylene and the antioxidant is (0.35-0.7):100; the ratio of the amount of substance of the ligand to the amount of substance of the catalyst is 1:1; and the ratio of the mass of the antioxidant to the mass of the low-density polyethylene and the antioxidant is (0.1-0.5):

100.

5. The method for preparing the cross-linked polyethylene insulation material with intrinsic self-repairing and recyclable properties according to claim 3, characterized in that: In the step (1), the catalyst is one of copper chloride and copper iodide; the solvent is one of toluene, o-dichlorobenzene and p-xylene; the ligand is 1,10-phenanthroline; and the peroxide is one of diisopropylbenzene peroxide, di(hexadecyl) dicarbonate and di-tert-butyl peroxide.

6. The method for preparing the cross-linked polyethylene insulation material with intrinsic self-repairing and recyclable properties according to claim 3, characterized in that: In the step (1), the temperature of the catalytic amination reaction is 115-125° C., and the time of the catalytic amination reaction is 80-120 min.

7. The method for preparing the cross-linked polyethylene insulation material with intrinsic self-repairing and recyclable properties according to claim 3, characterized in that: In the step (2), the furanyl small molecule is one of 2,2-di(2-tetrahydrofuranyl)propane, bis(2-methyl-3-furanyl)disulfide, di(2-furanyl)phosphine chloride and tri(2-furanyl)phosphine.

8. The method for preparing the cross-linked polyethylene insulation material with intrinsic self-repairing and recyclable properties according to claim 3, characterized in that: In the step (2), the ratio of the mass of the furanyl small molecule to the total mass of the low-density polyethylene and the antioxidant is (0.5-3.0):100; the ratio of the mass of the peroxide to the total mass of the low-density polyethylene and the antioxidant is (1.0-2.6):

100.

9. The method for preparing the cross-linked polyethylene insulation material with intrinsic self-repairing and recyclable properties according to claim 3, characterized in that: In the step (2), the order of post-absorption is furanyl small molecules and peroxide, the temperature of post-absorption treatment is 60-80°C, and the time of post-absorption treatment is 12-28h; the temperature of hot pressing treatment is 120-180°C, and the hot pressing time is 6-120min.

10. Use of the polyethylene insulation material according to claim 1 or 2 or the cross-linked polyethylene insulation material prepared by the method according to any one of claims 3 to 9 in the field of cable insulation materials.

Citation Information

Patent Citations

  • Cable insulation material with self-repairing function

    CN106750829A

  • Copper catalyzed amidation of polyolefins

    CN118974131A

  • Crosslinked polyethylene resin composition, crosslinked polyethylene resin and application thereof

    CN119081012A

  • Thermoplastic elastomer, method for producing the same, and electric wire and cable

    JP2014034615A

  • Process for modifying polymers

    US20180155480A1

Cited By

  • Flame-retardant and insulated low-voltage power cable and preparation method and application thereof

    CN121641576A

  • Crosslinked polyethylene flexible control cable for humanoid robot

    CN122245866A